Terahertz Magnetospectroscopy of Cyclotron Resonances from Topological Surface States in Thick Films of CdxHg1−xTe. Issue 1 (4th May 2020) - Otteneder, Maximilian; Sacré, Daniel; Yahniuk, Ivan; Budkin, Grigory V.; Diendorfer, Kilian; Kozlov, Dmitry A.; Dmitriev, Ivan A.; Mikhailov, Nikolay N.; Dvoretsky, Sergey A.; Bel'kov, Vasily V.; Knap, Wojciech; Ganichev, Sergey D.
Abstract : Herein, studies of the cyclotron resonance (CR) in thick Cd x Hg 1 − x Te films with different cadmium contents corresponding to materials with and without band inversion, as well as critical content corresponding to an almost linear energy dispersion are presented. The results demonstrate that the formation of 2D topological surface states requires sharp interfaces between layers with and without band inversion, in which case the corresponding CR is clearly observed for the out‐of‐plane orientation of magnetic field but does not show up for an in‐plane orientation. In contrast, all samples having more conventional technological design with smooth interfaces (i.e., containing regions of Cd x Hg 1 − x Te with gradually changing Cd content x ) show equally pronounced CR in both in‐plane and out‐of‐plane magnetic field revealing that CR is excited in effectively 3D states. Modeling of the surface states for different film designs supports main observations. In all samples, additional broad helicity‐independent resonances are observed, which are attributed to photoionization and magnetic freeze‐out of impurity states. Abstract : Herein, studies of the cyclotron resonance in Cd x Hg 1 − x Te films demonstrate that the formation of 2D topological surface states requires sharp interfaces between layers with and without band inversion. Exclusively for sharp interfaces, the corresponding CR is clearly observed for the out‐of‐plane orientation of magnetic field but does not show up for an in‐plane orientation.